Design and optimization of a MEMS quartz mass sensor array for biosensing - Zainuddin, Ahmad Anwar; Nordin, Anis Nurashikin; Md Ralib, Aliza Aini; Ab Rahim, Rosminazuin; Khan, Sheroz; Guines, Cyril; Chatras, Matthieu; Pothier, Arnaud (Institute of Electrical and Electronics Engineers Inc., 2018)
Most commercial quartz crystal microbalance (QCM) sensors are fabricated as a single AT quartz crystal device and are used for biosensor applications. This limits the sensor’s ability to perform detection of multiple targets at a single time. To overcome this we propose in this work, the design, optimization and simulation of a MEMS quartz mass (QCM) sensor array. A circular mass sensor placed in an array of four sensors with working electrode radius, r = 100ȝm and centre to centre distance between electrodes, s=2.5mm was designed. Based on COMSOL simulations, resonance frequency of 10.40MHz and mass sensitivity of 0.223 Hz.cm2.ng-1 in liquids was obtained. Simulations indicate the best placement of the quadruple MEMS sensors in an array such that their signals do not interfere with each other. Low degradation of resonance frequency up to 40 kHz was observed based on simulation results.